DOI: 10.14264/uql.2014.616
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Australia’s cultural history through archaeological geophysics

Abstract: The aim of this thesis is to develop and apply geophysical methods for Australian archaeology. The methods focus on magnetic susceptibility and ground-penetrating radar (GPR). The techniques are contextualised through application to the following four key archaeological questions: 1) Can magnetic susceptibility assist in resolving questions surrounding the potential downward movement of stone artefacts in rockshelter deposits? 2) Is human occupation persistent through the changing climatic regime associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…These most recent studies revealed a stone assemblage including late Pleistocene-aged grindstones, ground edge axes and ground ochres (Clarkson et al 2017). Subsequent detailed studies have included the analyses of the mid-Holocene shell midden layer (Woo 2020), magnetic susceptibility of the sediments (Lowe 2014), burial patterns (Lowe et al 2014), the archaeobotanics (Carah 2017;Florin et al 2022), Holocene-aged ochres (Cox 2013;Crough-Heaton 2021), flaked stone artefacts (McNeil 2016), ground stone assemblage (Hayes 2015) and bone points (Basiaco 2018;Langley et al 2023).…”
Section: The Madjedbebe Site Contextmentioning
confidence: 99%
“…These most recent studies revealed a stone assemblage including late Pleistocene-aged grindstones, ground edge axes and ground ochres (Clarkson et al 2017). Subsequent detailed studies have included the analyses of the mid-Holocene shell midden layer (Woo 2020), magnetic susceptibility of the sediments (Lowe 2014), burial patterns (Lowe et al 2014), the archaeobotanics (Carah 2017;Florin et al 2022), Holocene-aged ochres (Cox 2013;Crough-Heaton 2021), flaked stone artefacts (McNeil 2016), ground stone assemblage (Hayes 2015) and bone points (Basiaco 2018;Langley et al 2023).…”
Section: The Madjedbebe Site Contextmentioning
confidence: 99%
“…Following debate (e.g., Bowdler 2017;Clarkson et al 2018;Smith et al 2020;Veth 2017;Williams et al 2021;Wood 2017), public discourse in Australia has strongly adopted the findings from Madjedbebe, and the 65,000-year date is now routinely cited as the basis for the world's "longest continuous culture" in parliamentary documents, policy documents, government statements, and across the media. A multitude of specialist studies were forthcoming from this project-although, under current arrangements, researchers now seek direct approval from GAC to work on materials excavated from Madjedbebe (e.g., Crough-Heaton 2021; Langley 2021; Langley et al 2023;Litster 2022; and see the case study below), rather than obtaining access via the lead researcher, as was formerly the case (Basiaco 2018;Carah 2017;Cox 2013;Florin 2013Florin , 2020Florin et al 2020Florin et al , 2021Hayes 2015;Hayes et al 2021Hayes et al , 2022Lowe 2014;Marwick et al 2017;McNeil 2016;Moody 2016;Woo 2020).…”
Section: Gac Community Leadershipmentioning
confidence: 99%
“…Archaeological Research in the Alligator Rivers Region, Northern Territory, Australia August 2023 | Advances in Archaeological Practice | A Journal of the Society for American Archaeology study below), rather than obtaining access via the lead researcher, as was formerly the case(Basiaco 2018;Carah 2017;Cox 2013;Florin 2013Florin , 2020Florin et al 2020Florin et al , 2021Hayes 2015;Hayes et al 2021 Hayes et al , 2022Lowe 2014;Marwick et al 2017;McNeil 2016;Moody 2016;Woo 2020).…”
mentioning
confidence: 99%
“…Due to their strong association with anthropogenic fires, magnetic signals have the potential to be used as a proxy for mapping the spatial and temporal distribution of human occupation (e.g. Herries and Fisher 2010) through both field (Dalan 2007) and laboratory (Dalan and Banerjee 1998) studies.These techniques, particularly the analysis of the magnetic properties of sediments from excavations, have often been applied to rockshelter investigations, including occasionally in Australia (Lowe 2014;Marwick 2005). Far less common is the use of field magnetometry as a tool to investigate patterns of occupation in caves and rockshelters, although such methods have significant potential to map the spatial patterning of occupation within a site.…”
Section: Geophysicsmentioning
confidence: 99%